Erythrocyte sphingosine kinase regulates intraerythrocytic development of Plasmodium falciparum - Raj Kumar Sah (Nature Portfolio, 2021)
Abstract The sphingolipid pool is key regulator of vital cellular functions in Plasmodium falciparum a causative agent for deadly malaria. Erythrocytes, the host for asexual stage of Plasmodium, are major reservoir for Sphingosine-1-phosphate (S1P). Erythrocyte possesses Sphingosine kinase (SphK) that catalyzed its biosynthesis from sphingosine (Sph). Since, Plasmodium lacks SphK homologous protein it can be envisaged that it co-opts sphingolipids from both intraerythrocytic as well as extracellular pools for its growth and development. Herein, by sphingosine-NBD probing, we report that infected erythrocytes imports Sph from extracellular pool, which is converted to S1P and thereby taken by P. falciparum. Next, by targeting of the SphK through specific inhibitor N,N-Dimethylsphingosine DMS, we show a reduction in erythrocyte endogenous S1P pool and SphK-phosphorylation that led to inhibition in growth and development of ring stage P. falciparum. Owing to the role of S1P in erythrocyte glycolysis we analyzed uptake of NBD-Glucose and production of lactate in DMS treated and untreated plasmodium. DMS treatment led to decreased glycolysis in Plasmodium. Interestingly the host free Plasmodium did not show any effect on glycolysis with DMS treatment indicating its host-mediated effect. Further to understand the in-vivo anti-plasmodial effects of exogenous and endogenous erythrocyte S1P level, Sphingosine-1-phosphate lyase (S1PL) inhibitor (THI), S1P and SphK-1 inhibitor (DMS), were used in Plasmodium berghei ANKA (PbA) mice model. DMS treatment led to reduction of endogenous S1P conferred significant decrease in parasite load, whereas the plasma level S1P modulated by (THI) and exogenous S1P have no effect on growth of Plasmodium. This suggested erythrocyte endogenous S1P pool is important for Plasmodium growth whereas the plasma level S1P has no effect. Altogether, this study provides insight on cellular processes regulated by S1P in P. falciparum and highlights the novel mechanistically distinct molecular target i.e. SphK-1.